The Impact of Poverty on First Nations Mothers Attending a Parenting Program - Harris, Barbara; Russell, Mary; Gockel, Annemarie (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2007)
Urban Aboriginal mothers’ experiences with Family Preservation Services indicate that while such interventions ameliorate the challenges they face, poverty is not adequately addressed. Prominent are the importance of prevention; attention to process; cultural context; and attention to actual needs, however, First Nations mothers (a) feel lucky when they get things they need, (b) feel ‘inadequate’ about the inability to manage ﬁnances, and, (c) perceive the lack of support in meeting needs to be a result of racism. As well, poverty often leads to forced compromises which can perpetuate risk of coming to the attention of child welfare.